2019
DOI: 10.2967/jnmt.118.224303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Lower-Limb Imaging in 68Ga-PSMA PET/CT for Patients with Prostate Cancer

Abstract: Our purpose was to determine whether there is a clinical benefit to add lower-limb imaging in 68 Ga-labeled prostate-specific membrane antigen (PSMA) PET/CT scans for patients with prostate cancer. Methods: In total, 701 patients with prostate cancer who underwent 68 Ga-PSMA PET/CT were evaluated retrospectively. All patients underwent additional lower-limb imaging. Images were reanalyzed by experienced nuclear medicine physicians, and metastatic sites were documented. The prostate-specific antigen (PSA) leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…All but one of these patients had already known extensive bone disease, and planned management was changed in this only one patient. Simsek et al also evaluated the clinical impact of including the lower limbs in 68 Ga-PSMA-11 PET/CT scans for prostate cancer patients (29). They similarly found that lower-limb imaging did not change the metastatic status of disease or significantly affect the therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one of these patients had already known extensive bone disease, and planned management was changed in this only one patient. Simsek et al also evaluated the clinical impact of including the lower limbs in 68 Ga-PSMA-11 PET/CT scans for prostate cancer patients (29). They similarly found that lower-limb imaging did not change the metastatic status of disease or significantly affect the therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a significant and useful impact of total-body versus whole-body imaging appears unlikely. Of note, in a symptomatic patient, it could be beneficial to include lower-limb imaging for possible palliative therapies (29).…”
Section: Discussionmentioning
confidence: 99%
“…These observations were in line with two smaller-scaled studies. Simsek et al reported in 701 PCa patients also low rates (8.7 % , n = 61) of positive lesions in the lower extremities [3]. Similarly, Pomykala et al analyzed 388 PCa patients and reported 5.0 %-rate (n = 18) of positive lesions in the lower extremities [4].…”
Section: Discussionmentioning
confidence: 97%
“…In these patients multiple metastases in other locations were present. The authors concluded that imaging of the lower extremities were not mandatory due to missing therapeutic consequences [3]. However, these studies were limited by the smaller study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…68Ga-PSMA PET-CT was performed at 45-60 min after an intravenous injection of approximately 185 MBq of 68Ga-PSMA on a dedicated PET-CT scanner (Biograph TruePoint PET/CT; Siemens Healthcare. Erlangen, Germany), as we described previously (19). An iodine-based oral contrast agent was administered to all patients.…”
Section: Ga-psma Synthesis and Pet/ct Acquisitionmentioning
confidence: 99%